Innovative approach to simulating the biodeterioration of industrial cementitious products in sewer environment. Part II: Validation on CAC and BFSC linings. (January 2016) - Lavigne, Matthieu Peyre; Bertron, Alexandra; Botanch, Catherine; Auer, Lucas; Hernandez-Raquet, Guillermina; Cockx, Arnaud; Foussard, Jean-Noël; Escadeillas, Gilles; Paul, Etienne
Abstract: The development of a new test method for evaluating the resistance of manufactured cementitious products to biogenic acid attack, labeled BAC-Test for Biogenic Acid Concrete Test, was reported in Part I of this paper. The performance of the test in terms of sulfur-oxidizing bacteria selection and acid and sulfate production has been validated previously. In this second part, the representativeness of the degradation mechanisms of the cementitious materials is explored. Two segments of industrial pipes – ductile cast iron coated with cementitious linings (blast furnace slag cement (BFSC) and calcium aluminate cement (CAC) mortars) – were exposed to the test for 107 days. Then linings were analyzed by SEM coupled with EDS, EPMA, and XRD. Significant differences between BFSC and CAC linings were highlighted. Abundant cracking of the BFSC lining was observed, caused by precipitation of secondary ettringite, while no cracking was observed in the CAC lining. The CAC outer layer was composed mainly of AH3 gel. The decalcification front was deeper in the BFSC matrix than in the CAC one.